Planning for environmental water allocations: an example of hydrology-based assessment in the east Rapti River, Nepal - Smakhtin, Vladimir U.; Shilpakar, R.L. (International Water Management Institute, 2005)
Although the protection of the aquatic environment is high on the world water resources agenda, most developing countries still lack the technical and institutional capacity to establish environmental water allocation practices and policies. The existing methods of assessment of environmental water allocations are either complex and resource-intensive or not tailor-made for the specific conditions of a particular country or region. To promote emerging concepts of environmental flow assessment and management, it is important to change the dominant perception that environmental demand is the least important and create awareness among responsible authorities about existing methodologies and processes that should be followed. This report presents some of these approaches and illustrates their applicability in the specific context of the East Rapti River basin, which features one of the main tourist attractions of Nepal, the Chitwan National Park.